1984
DOI: 10.1093/ajcn/39.2.289
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of type of dietary carbohydrates with copper deficiency

Abstract: The present study was designed to determine if the more severe copper deficiency in rats fed sucrose and fructose, as compared to starch, is due to a specific effect of the fructose or to a nonspecific effect of any simple carbohydrate. Seventy weanling male rats were fed, for 9 wk, copper-deficient diets or copper-supplemented diets containing either 62% starch, fructose, or glucose. Decreased hematocrit, serum copper, and ceruloplasmin concentrations but increased heart and liver weights, total liver lipid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(36 citation statements)
references
References 18 publications
3
31
0
2
Order By: Relevance
“…Follow-up work indicated that when diets with fructose, glucose or starch were combined with copper deficiency, both glucose and fructose raised plasma cholesterol levels. However, severity of copper deficiency and mortality were much greater with fructose as opposed to glucose feeding (65), suggesting that the exacerbation of copper deficiency by sucrose was due to the fructose component. More recent work (66) indicates that the effect of fructose may be at the level of absorption, whereby copper deficiency induces upregulation of the copper transporter Ctr1, but this effect is eliminated by high fructose feeding (Figure 1).…”
Section: Fructose Lipids and Copper Metabolismmentioning
confidence: 93%
“…Follow-up work indicated that when diets with fructose, glucose or starch were combined with copper deficiency, both glucose and fructose raised plasma cholesterol levels. However, severity of copper deficiency and mortality were much greater with fructose as opposed to glucose feeding (65), suggesting that the exacerbation of copper deficiency by sucrose was due to the fructose component. More recent work (66) indicates that the effect of fructose may be at the level of absorption, whereby copper deficiency induces upregulation of the copper transporter Ctr1, but this effect is eliminated by high fructose feeding (Figure 1).…”
Section: Fructose Lipids and Copper Metabolismmentioning
confidence: 93%
“…and plasma and hepatic triglyceride concentrations and thus exaggerate hepatic inflammation [20,21]. It is suggested that dietary fructose, in addition to its metabolic effects, may also impair gut absorption of copper by inhibiting the copper transporter located in the duodenal and proximal jejunum [10,22].…”
Section: Discussionmentioning
confidence: 99%
“…Neste contexto, o tipo de carboidrato da dieta constitui também um fator importante na utilização do cobre, sendo a frutose o mais investigado, principalmente em estudos de deficiência deste mineral (Reiser et al, 1983;Fields et al, 1984;Fields et al,1986;Werman & Bhathena, 1992).…”
Section: Aspectos Metabólicos E Fisiológicos Do Cobreunclassified
“…Experimentos delineados para testar os efeitos do consumo de frutose ou amido na deficiência de cobre têm mostrado que ratos machos alimentados com dietas deficientes em cobre contendo frutose apresentam sinais de deficiências mais graves do que os ratos alimentados com amido (Reiser et al,1983;Fields et al, 1984). Acrescentando-se o fato de que ratas alimentadas com dietas deficientes em cobre parecem estar protegidas desses efeitos (Fields et al, 1986;Werman et al, 1995), tem-se sugerido que os animais metabolizam frutose de forma diferente, dependendo do sexo.…”
Section: Aspectos Metabólicos E Fisiológicos Do Cobreunclassified